First record of the genus Bezzia in Chile, with a description of a new species of the venustula group (Diptera: Ceratopogonidae) Primer registro del género Bezzia en Chile, con la descripción de una especie nueva del grupo venustula (Diptera: Ceratopogonidae) - GUSTAVO R. SPINELLI (Revista Chilena de Historia Natural, 2001)
A new species of ceratopogonid diptera from central Chile, Bezzia chilensis, is described and illustrated based on an adult male and five female specimens, and also the widespread species Bezzia nobilis (Winnertz) is firstly recorded for the country Sobre la base de ejemplares adultos macho y hembras, se describe una nueva especie de díptero ceratopogónido de la zona central de Chile, Bezzia chilensis. Además, se registra por primera vez para este país a la especie de amplia distribución Bezzia nobilis (Winnertz)